Bulk fill resin restoration: Clinical considerations and case report - Feitosa, Fernanda Alves [UNESP]; Esteves, S. R. [UNESP]; Crastechini, E. [UNESP]; Ferraz Caneppele, T. [UNESP]; Bresciani, E. [UNESP] (SciDoc Publishers, 2018)
The objective of this paper was to present a case report of bulk fill resin restoration, discussing treatment planning and clinical protocol, presenting the follow-ups, and discussing the available literature on the issue. The case report presents a resolution for an extensive carious lesion on the distal surface of the second left maxillary premolar using bulk fill composite. Cavity preparation was made with diamond and carbide round burs. After rubber dam isolation was performed, sectional matrix Uni-matrix system and rubber wedge were positioned. Cavity conditioning was performed by etching enamel for 30s and dentin for 15s with 37% phosphoric acid. Cavity was further washed with air/water spray and water excess was removed with cotton ball. The adhesive system was actively applied for 20s, followed by a 5s air blast and light curing for 10s. A single 4mm resin composite (SDR bulk fill – Dentsply) increment was inserted into the cavity being dispensed at the deepest cavity portion and light cured for 20s. Approximately 2mm room was left to allow the insertion of a layer of nanofilled resin to finish the restorative procedure. Finishing and polishing of restoration were performed after 7 days in service and the restoration was evaluated according to Modified USPHS and FDI parameters. After 6 months and 1 year, new assessments were performed following parameters previously cited. No changes in parameters from baseline were detected. The restoration was rated as successful at both evaluation periods.
Keywords: Bulk fill composites; Class II restoration; Clinical evaluation; Posterior restoration